(untitled) (Fiep Bulletin - online, 2011)
This study aims is to identify cases of AIDS in elderly patients from a referral service. It is a documental research in the Department of Specialized Care, University Hospital Lauro Wanderley, João Pessoa, Paraíba, Brazil. The study involved 400 medical records of patients with diagnoses of HIV / AIDS for the tracking of cases of elderly people of both sexes. The data were analyzed using statistical procedures and showed that: 50% were male and 50% female and as marital status: (66.6%) are married; (16.7%) are widowed; (16.7%) are single, as the HIV status of HIV/AIDS.